Knowledge and attitude on infant vaccination among university staff in Malaysian public university - Shaipuzaman, Nurulain Atikah; Abdul Rahman, Haliza (Taylor Francis, 2022)
Objective: To determine the knowledge and attitude on infant vaccination among a couple of Universiti Putra Malaysia (UPM) staffs in Serdang, Selangor. Methods: A cross-sectional study was carried out involving 97 respondents. A cluster sampling technique for the categorization of the faculty in UPM to science-based and non-science-based is used. Then, fishbowl technique was adopted in selecting the faculty from the two categorizations, which consists of 1) science-based: Faculty Biotechnology and Science Biomolecule and Faculty of Science; 2) non-science-based: Faculty of Economics and Management and Faculty of Language and Communication. Consequently, a simple random method was used to choose the respondent based on the inclusion and exclusion criteria. Data on socio-demographic characteristic, knowledge and attitude regarding infant vaccination were collected using a modified and pretested questionnaire. The data then were analyzed using SPSS version 22. Results: Of 97 respondents, 78 (80.4%) had high knowledge, and 49 (50.5%) have moderate attitude regarding infant vaccination. Overall, science-based faculty and non-science-based faculty prevalence of refuse infant vaccination was 2.1%, 6.5%, respectively. There was a significant association between educational level and the knowledge (p < .05, p = .019). However, there was no significant association between socio-demographic and attitude. Other than that,, there was no association between knowledge and attitude among these two different types of faculty (P > .05, p = .256, p = .597). Conclusion: Effort are needed for focusing on health education campaign with collaboration between health-care professionals, social media and community to improve their awareness for immunization.